Canine Transmissible Venereal Tumor: Treatment Review and Updates - Palagan Senopati Sewoyo, I Made Kardena (Revista Electronica de Veterinaria, 2022)
Summary and Purpose: The increased resistant cases for treatment of canine transmissible venereal tumor (CTVT) have resulted in the emergence of several new alternatives. The current and most common therapeutic uses for the treatment of CTVT were reviewed and discussed in this article. Several new therapies, both clinically tested and currently in clinical trials, were also discussed. In addition, therapies, including the agents that were not effective for treating CTVT also being presented for future consideration in relation to the treatment usage.Conclusion: New treatments for canine transmissible tumors are likely promising, especially for the cases that have developed resistance to certain treatments although these agents and/or therapies need to be more clarified in future studies. Nevertheless, the agents or thrapies that are not effective in treating CTVT are not expected to be used in treating the cases of CTVT.